Report of the second meeting of the planning group for the coordination of acoustic surveys off Northwest Africa. Dakar, Senegal, 28-29 Oct 2003 - FAO, Roma (Italia) (Roma (Italia), 2005)
Sumario (En, Fr)
Ilus.
Keywords: RECURSOS PESQUEROS; ENCUESTAS; INVESTIGACION; PLANIFICACION; AFRICA